Effect of Nitrogen on Seed Yield, Protein Content and Nutrient Uptake of Soybean (Glycine max L.) - Morshed, RM; Rahman, MM; Rahman, MA (Journal of Agriculture & Rural Development, 2008)
A pot experiment was conducted at the experimental space of Botany Department, Jahangirnagar University, Savar, Dhaka during rabi season 2004-2005 to determine the effect of nitrogen (N) on yield, protein content and nutrient uptake of soybean using G-2 (Bangladesh soybean-4) as test crop. Rates of N used were 0 (N1), 10.58 (N2), 15.87 (N3), 21.16 (N4), 26.45 (N5) and 31.74 (N6) kg ha-1 equivalent to 0, 50, 75, 100, 125 and 150% of recommended N doses. Seeds were inoculated with Bradyrhizobium inoculum before sowing. Nitrogen application progressively and significantly increased the yield of soybean upto the N rate of 26.45 kg ha-1 where the highest seed yield of 6.85 g plant-1 was obtained. Nutrient uptake and protein content in seeds also increased with increasing levels of N (up to the same rate of 26.45 kg N ha-1). It is concluded that application of 25% higher N over BARC recommendation could give maximum seed yield, protein content and nutrient uptake by soybean seed. Key words: Soybean, nitrogen, yield, nutrient, protein. doi:10.3329/jard.v6i1.1652 J Agric Rural Dev 6(1&2), 13-17, June 2008